An improved Three-Level Zero-Voltage and Zero-Current Switching PWM DC-DC converter for battery charger - Jangwanitlert, A. (My University, 2014)
This paper describes a 2-kW Three-Level Zero-Voltage and Zero-Current Switching (TL-ZVZCS) PWM dc-dc converter for battery charger. To solve the disadvantages from TL-Zero-Voltage Switching (ZVS) such as a circulating primary current and parasitic voltage ringing on the dual diodes rectifier, a proposed simple auxiliary circuit is composed of a small capacitor with two small diodes is put on the transformer secondary side to achieve ZVZCS conditions of primary switches and to clamp secondary voltage rectifier. The auxiliary circuit does not give any losses in components and additional active switches, which provides the proposed circuit converter more effective and efficient. Moreover, this paper describes the key operation waveforms, operational modes and design considerations. The concept idea is verified by the MATLAB simulation. © 2014 IEEE.
Keywords: auxiliary circuit; PWM; three-level; ZVZCS